2006
DOI: 10.1155/2006/169625
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba Species Keratitis in a Soft Contact Lens Wearer Molecularly Linked to Well Water

Abstract: An otherwise-healthy 14-year-old female soft contact lens wearer, who lived in a rural area where the tap water source for the home was a well, presented to a community hospital with a four-week history of progressive redness, swelling and blurred vision of her left eye despite treatment with topical neomycin and corticosteroids. A dendritiform corneal epithelial lesion, corneal edema and inflammation in the anterior chamber were noted on initial examination, and treatment for herpes simplex keratouveitis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…32 Acanthamoeba spp. are a common microbial inhabitant of water sources, including wells and groundwater sources 28, 33, 34 and studies have shown an increased risk for AK associated with showering, using hot tubs, and swimming with contact lenses. 35, 36 Other studies have shown associations with AK and water quality, case-patient geography, and water storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…32 Acanthamoeba spp. are a common microbial inhabitant of water sources, including wells and groundwater sources 28, 33, 34 and studies have shown an increased risk for AK associated with showering, using hot tubs, and swimming with contact lenses. 35, 36 Other studies have shown associations with AK and water quality, case-patient geography, and water storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…24 The incidence of CLPU was always higher with extended wear asymptomatic (extended wear vs. daily wear: up to 25% vs. up to 20%) or symptomatic (extended wear vs. daily wear: up to 6% vs. up to 3%) contact lens wear compared to daily wear, even with the use of silicone hydrogel contact lenses. 24 Multiple genera and species are associated with contact lens induced MK, including Pseudomonas aeruginosa, [25][26][27][28] Staphylococcus aureus, 27 Acanthamoeba species, [27][28][29][30][31] and fungi especially Fusarium spp. Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%